Would it be legally justified to impose vaccination in Israel? Examining the issue in light of the 2013 detection of polio in Israeli sewage - Shelly Kamin-Friedman (BMC, 2017)
Abstract Background The detection of wild poliovirus in Israeli sewage in May 2013 led the health authorities to decide that children who had been vaccinated with IPV would also be vaccinated with OPV. The decision sought to protect vulnerable Israeli individuals who were either not vaccinated with IPV or who suffered from an immune deficiency, to preserve Israel's status as a polio-free country, to prevent the virus' "exportation" into vulnerable polio-free countries, and to participate in the global efforts toward the eradication of polio. After a massive public persuasion campaign, 79% of the children born after 2004 were vaccinated as well as 69% of the children residing in central Israel. A 2014 State Comptroller Report stated that the Ministry of Health should draw conclusions from the low compliance rates in certain Israeli regions. Goals The article seeks to examine the legal legitimacy of mandatory vaccination in the service of eradicating a contagious disease (as opposed to preventing a pandemic outbreak), which was one of the objectives in the 2013 Polio case. It more specifically relates to current Israeli law as well as to a hypothetical new public health law which would authorize health officials to oblige vaccination and enforce this through the use of criminal sanctions. Method Qualitative content analysis through the interpretation of court judgements, laws, legislative protocols, health ministry guidelines and documented discussions of the Advisory Committee on Infectious Diseases and Immunization. Main findings and conclusion A mandatory vaccination backed by criminal sanctions in the service of the eradication of contagious diseases would probably be perceived as infringing on the constitutional right to autonomy to a greater extent than necessary according to Israeli law and case law precedents. There may be some added value inherent in a new public health law which would authorize health officials to oblige vaccination where nonrestrictive measures have been ineffective. However, the law should also specify a variety of sanctions to accompany the enforcement of mandatory vaccinations which would be formulated from least to most restrictive according to the "intervention ladder" concept. The law should also describe the circumstances which would justify the implementation of each and every sanction as well as the procedural safeguards designed for established decisions and fairness toward the individual(s) whose rights are infringed by the application of these sanctions.